2020
DOI: 10.1111/dth.14439
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of adult atopic dermatitis patients according to disease characteristics and demographics

Abstract: Little is currently known about possible associations between disease specific characteristics of atopic dermatitis (AD) and use of medical treatments. We explored the use of AD treatments within the past 12 months in Danish adults according to distinct patient characteristics. Patients who had received a diagnosis of AD in a hospital in-or outpatient setting as adults were surveyed and data cross-linked to a national prescription registry. AD severity was measured by the Patient-Oriented SCORing Atopic Dermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This study showed that patients with uncontrolled AD receiving topical therapy had worse QoL, symptom burden, and work impairments versus those with controlled AD, expanding upon previous AD DSP analyses that showed similar findings in patients with moderate to severe disease [19,20]. The lower DLQI scores among patients receiving topical therapy alone compared with topical plus systemic therapy observed in this study have also been previously described in a Danish registry study of patients receiving topical corticosteroids alone versus combined oral and topical treatment [29]. Findings from the present study further highlight the unmet need for well-tolerated topical AD therapies that offer disease control.…”
Section: Discussionsupporting
confidence: 82%
“…This study showed that patients with uncontrolled AD receiving topical therapy had worse QoL, symptom burden, and work impairments versus those with controlled AD, expanding upon previous AD DSP analyses that showed similar findings in patients with moderate to severe disease [19,20]. The lower DLQI scores among patients receiving topical therapy alone compared with topical plus systemic therapy observed in this study have also been previously described in a Danish registry study of patients receiving topical corticosteroids alone versus combined oral and topical treatment [29]. Findings from the present study further highlight the unmet need for well-tolerated topical AD therapies that offer disease control.…”
Section: Discussionsupporting
confidence: 82%
“…While the prevalence of the identified subgroup of patients remains to be elucidated in a real-world setting, a significant proportion of patients who are candidates for systemic therapy in clinical practice might fall within this identified group of patients with AD. Indeed, data from real-world clinical practice suggest that patients with moderate-to-severe AD have generally lower BSA involvement as compared to patients enrolled in clinical trials and an affected mean BSA more in line with patients in the BSA 10–40% than in the BSA > 40% subgroup of the current analysis [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies in other countries also reported a high prevalence of SCS use among patients with AD; however, SCS use in Korea seems to be higher than that in other countries, especially in adults. In Denmark and Japan, approximately 12% and 30% of adults with AD received SCSs, respectively, whereas approximately 60% in Korea do 9 10 .…”
mentioning
confidence: 99%